(untitled) (Journal of Educational Sciences, 2024)
In the contemporary era of abundant information, cultivating research competence has become an essential skill in higher education. This study, conducted at Korkyt Ata Kyzylorda University in Kazakhstan, employs a mixed-methods approach to assess factors influencing the development of research competence among students and teachers. The research utilizes a survey created on the Google Form platform to gather quantitative data from 120 participants and qualitative insights from interviews with 12 students. The study aims to evaluate participants’ understanding of terms like “proficiency” and “competency”, explores the role of teachers in fostering research competencies, and examines the impact of technology on research skills. The findings reveal diverse perspectives among students, emphasizing the multifaceted nature of research competence. Challenges include information overload and technical aspects of data analysis. Students value the integration of research competence in courses but desire a more structured approach. The study highlights the crucial role of teachers in motivating students and fostering a research culture. Results provide valuable insights for educational development and curriculum design in enhancing research competence within higher education. Keywords: Research competence, higher education, mixed methods, student perceptions, teacher influence, educational development.